عقیدہ ختم نبوت: لغوی و شرعی تفہیم، نقلی و عقلی دلائل، اجماع امت، اور مدعیان نبوت کے شبہات کا تنقیدی جائزہ: Doctrine of Finality of Prophethood: Lexical and Jurisprudential Understanding, Scriptural and Rational Evidences, Consensus of the Ummah, and a Critical Examination of the Doubts Raised by Claimants of Prophethood - Syed Iftikhar Ali Gilani; Dr. Tayyaba Razzaq (International Research Journal of Arabic and Islamic Studies, 2024)
Allah started the chain of Prophethood from Hazrat Adam A.S and ended up with the Holy Prophet Muhammad (Pbuh) Belief in Khatm-e-Nubuwwat is one of the basic and important articles of faith. From the Holy Prophet time to this day every Muslim has the belief that Muhammad is the last Prophet of God without any doubt. The whole Muslim Ummah has coherence on the belief of Khatm-e-Nubuwwat. Belief in the end of prophethood is the basic belief of Muslims. False prophets have been attacking this belief since the demise of the Holy Prophet (Pbuh). Mirza Ghulam Ahmad Qadiani claimed prophethood in the subcontinent but the scholars declared it to be constitutionally false by practical and academically arguments. They are constantly working to promote and harm the Muslims. Now these Qadiani and anti-Islamic forces have re-established themselves and are targeting the younger generation. The main purpose of this paper is to highlight the important contemporary challenges, to make the new generation aware of this tribulation and to connect them with the Qur'an, Sunnah and Seerat-e- Mubarkah. This researh paper concluded that all the expounders and exegetics have concord on the meanings of Khatm-e-Nubuwwat; there is neither any type of Prophet nor any sort of messenger after Hazrat Muhammad ((Pbuh)). It is also concordat that there is no other interpretation or appropriation in the meanings of the word Khatm-e-Nubuwwat.Similarly, the ummah of the Prophet (Pbuh) is the last ummah.